Yield loss assessment of chickpea caused by botrytis gray mold through fungicide (Bavistin) spray - Rashid, M. H.; Khalequzzaman, K. M.; Kashem, Md Abul; Alam, M. J.; Islam, M. S.; Yusop, Mohd Rafii; Latif, Mohammad Abdul (Marsland Press, 2013)
An experiment was conducted to assess the yield loss of chickpea caused by Botrytis gray mold (BGM) through fungicide spray at Pulses Research Centre, Bangladesh Agricultural Research Institute, Ishurdi, Pabna, Bangladesh. Sixteen entries were evaluated following RCB design with three replications. Out of 16 tested germplasms, eight germplasms (92040*52, FLIP97-530 CLIMS, 94-012*98V4006, FLIP98-106C, Gully, FLIP94-509C, 97020-1489 and S95425) showed resistant reaction, while eight and one entries showed susceptible and highly susceptible, respectably, in fungicide sprayed plot. The highest yield increase over BGM inoculated plot were observed in BARWON*98CIH4007 (180.49%) and 97020-1489 (157.96%). The lowest yield increase over BGM inoculated plot were recorded in HEERA*98CZH4010 (6.39%) and 94-012*98V4006 (8.93%) genotypes.